1999
DOI: 10.1182/blood.v93.11.3913
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Anaplastic Lymphoma Kinase (ALK) Protein Expression in Adults With Anaplastic Large Cell Lymphoma

Abstract: Anaplastic large cell lymphoma (ALCL) is an aggressive lymphoma that is frequently associated with the t(2;5)(p23;q35), resulting in expression of a fusion protein, nucleophosmin-anaplastic lymphoma kinase (NPM-ALK), which can be detected by either monoclonal or polyclonal antibodies to the ALK protein. The clinical features of adults with ALCL are incompletely described, and the prognostic factors that are useful for predicting survival remain unclear. This report describes the clinical and laboratory finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
10
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 405 publications
(123 citation statements)
references
References 50 publications
5
101
10
1
Order By: Relevance
“…One of the limitations of our study relates to the fact that we did not separate the various subtypes of PTCL in our analysis. Increasingly, the various subtypes of PTCL are recognized as a biologically diverse group of conditions and 'lumping' them together may potentially obscure their distinct natural histories (5,21). Nonetheless, with the exception of ALK-1 positive anaplastic large-cell lymphoma, which has a favorable outcome, the prognosis of the other subtypes of PTCL is uniformly poor (20).…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of our study relates to the fact that we did not separate the various subtypes of PTCL in our analysis. Increasingly, the various subtypes of PTCL are recognized as a biologically diverse group of conditions and 'lumping' them together may potentially obscure their distinct natural histories (5,21). Nonetheless, with the exception of ALK-1 positive anaplastic large-cell lymphoma, which has a favorable outcome, the prognosis of the other subtypes of PTCL is uniformly poor (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, since they are of B-cell lineage, do not in most cases express ALK and have nothing in common with the biological entity we recognize as anaplastic large cell lymphoma (ALCL), the use of the term 'pleomorphic' may be more appropriate than 'anaplastic' to avoid confusion with T-cell ⁄ null ALCL, which has a favourable clinical outcome in contrast to the inferior survival characteristics of DLBCL. 20,21 Recent studies of the molecular pathogenesis of DLBCL have suggested that aberrant activity of the somatic hypermutation mechanism may underlie many cases. 22 This may account for the lack of a dominant translocation mechanism in DLBCL and may explain the diversity of this group of lymphomas.…”
Section: 'Blastoid' Mantle Cell Lymphomamentioning
confidence: 99%
“…Subsequent expression of the anaplastic lymphoma kinase (ALK) protein is associated with an excellent prognosis. [15][16][17][18] In contrast, ALK-negative ALCL shows a variable prognosis 15 and a significantly lower expression of epithelial membrane antigen (EMA) and the cytotoxic phenotype proteins granzyme B and ⁄ or T-cell intracytoplasmic antigen (TIA)-1. [19][20][21][22][23] Thus, ALK-positive ALCL is a well-defined biological and clinical entity, but ALK-negative ALCL is more heterogeneous than hitherto assumed and needs further investigation.…”
mentioning
confidence: 99%